Türk Soylu Öğrencilerin Türkiye Türkçesi Sözlü Anlatım Çalışmalarının “Konuşma Becerisi Değerlendirme Ölçeği”ne Göre Analizi: Gagauz Örneği / Analysis of Turkic Students Verbal Expression Studies in Turkey Turkish Language by “Speaking Skill Assessment Scale” - Kurt, Berker (Journal of History Culture and Art Research, 2017)
Abstract In this study, the situation of the Turkic students’ verbal expressions of Turkey Turkish was evaluated with the special action of Gagauz Turks. The research findings reveal that Gagauz Turks depend on their mother language in terms of word choice, pronunciation, emphasis and sentence structure in verbal expressions. The similarity between Gagauz Turkish and Turkey Turkish is the main determinant for this situation. Research findings show that if the students were not to comprehend the similarities between the two languages this would have a negative impact on the verbal expression of Turkey Turkish. Therefore, as a result of the research, it is concluded that in order to improve the speaking ability of Turkey Turkish in teaching Turkic, it is necessary to take into account the mother language features that the target language has and to plan teaching accordingly. Öz Bu çalışmada Türk soylu öğrencilerin Türkiye Türkçesi sözlü anlatımlarındaki durumları Gagauz Türkleri özelinden hareketle değerlendirilmiştir. Araştırma bulguları, Gagauz Türklerinin sözlü anlatımlarında sözcük seçimi, telaffuz, vurgu ve cümle yapısı açısından ana dillerine bağlı kaldıklarını ortaya koymaktadır. Bu durumun oluşmasında Gagauz Türkçesi ile Türkiye Türkçesi arasındaki benzerlik önemli bir etkendir. Araştırma bulguları, öğrencilerin iki dil arasındaki benzerlik ve farklılıkları yeterince kavrayamamış olmalarının Türkiye Türkçesi sözlü anlatımlarını olumsuz olarak etkilediğini göstermektedir. Dolayısıyla, araştırma sonucunda, Türkiye Türkçesinin Türk soylulara öğretiminde konuşma becerisinin geliştirilmesi için hedef kitlenin sahip olduğu ana dil özelliklerinin göz önünde tutulması ve öğretimin buna göre planlanması gerektiği sonucuna varılmıştır.